Masculinidades e violências em narrativas de vida de jovens em conflito com a lei - Andrêo, Caio [UNESP] (2014)
The current protagonism of male gender youths in violent acts have been verified in several studies and appointments that lead them as the main victms and authors of such acts, especially at the underprivileged sections of society. Although this data is not apparently surprising the relation between masculinity and violence has not been focused and, therefore, still be naturalized limiting all discussions concerning this issue. In this way, this survey aims at describing the construction process of masculinities and its interface with violence, taking into account narratives from youths who had commited an offense. For this, we interviewed four teenagers (aged varied from 14 to 16 years old) who had been sent or had already spent time at a young offenders’ institution, located in a city in the countryside of São Paulo State. Their narratives took between thirty to sixty minutes and were recorded and then transcribed. The analises were conducted based on the narrative conceptions of Mikhail Bakhtin, Jerome Bruner and other authors who highlight, from a dialogic perspective, narrative productions as sources of discourses which uncover subjetivation processes as well as in studies about masculinities. The results suggest that the relation between masculinities and violence is more of a belief than a fait accompli. In spite of being extremely exposed to violence and its variations, and performing a certain expected way to be man, based on strength, aggressiveness and rationality all over their lives, the narratives pointed out other modes of subjetivation not necessarily connected to being violent, despite of this notion still be present in their discourses about life, the others and himself